Induction of hypersensitive necrosis at high temperatures by generation of reactive oxygen forms in virus resistant tobacco - Király, Lóránt (Acta Biologica Szegediensis, 2005)
Tobacco (Nicotiana tabacum cv. Xanthi nc) resistant to Tobacco mosaic virus (TMV) displays a hypersensitive response (HR) following virus infection, characterized by localized necrotic lesions around infection sites at ambient temperatures (e.g. 20°C). We have demonstrated that application of chemical compounds that generate reactive oxygen species (ROS), such as the riboflavin/methionine and glucose/glucose oxidase systems or H2O2 treatment induce HR-type necroses in leaves of Xanthi-nc tobacco infected with TMV even at high temperatures (30°C), when both necrosis and virus resistance are impaired. It was possible to suppress chemically induced HR-type necrotization at 30°C by application of antioxidants like superoxide dismutase (SOD) and catalase (CAT). Importantly, high TMV levels at 30°C did not differ in infected plants, regardless of the presence or absence of HR-type necrotization. Levels of one of the ROS, superoxide (O2·-), activity of NADPH-oxidase and expression of a tobacco NADPH-oxidase gene responsible for O2·-production were significantly lower in leaves of infected and healthy Xanthi-nc tobacco at 30°C, as compared to 20°C. It is concluded that development of HR-type necroses caused by TMV infection depends on a certain level of superoxide and other ROS, while suppression of virus multiplication in resistant tobacco is associated with low temperature but seems to be independent of HR-type necrotization.